O direito premial trabalhista como perspectiva para o futuro do trabalho - Daniela Rodrigues Machado (2016)
The argument of this dissertation intends to analyze without the pretense of finitude the outline of elements working, worker and Premial Employment Law. It aims to demonstrate the compatibility of the current time with the implementation of premial instruments by the utilitarian character of these in a society that calls for effective results. It starts historically contextualizing work over time, from its etymology, its unfolding in time and space, the forms already tried and phenomena that interfere in the formation of labor relations, such as flexibility, deregulation and globalization. It will be subject of discussion also the non-payment of labor credit. Then there will be an analysis of the present situation in the world of labor relations and the indication of premial mechanisms to induce greater compliance with law. This initial context justifies the importance of this research in a society that postulates for new answers. Further will be objects of analysis, specifically, reward instruments: incentives, gratifications and positive sanctions, its implications and what is its importance in the labor juridical science as a means of promoting ethics in labor law relations. The aim is to establish new debates and raise arguments about Premial logic, which is an element of great utility, as is entirely consistent with a society that claims results. These mechanisms assume that reward in the case of labor law, the employer must act according to the rule described in the law. It will also be discussed positive and negative sanctions and the need to exist concurrently. By the Premial logic, reward acts as an incentive for voluntary compliance with the standard, which is characterized as a true means of conflict prevention, because, the employer aware of the benefits complies with the legislation. Thus, the Premial Employment Law harmonizes with a future of new, more profitable and fair answers.